Proceedings of the Conference on Extreme Science and Engineering Discovery Environment: Gateway to Discovery 2013
DOI: 10.1145/2484762.2484763
|View full text |Cite
|
Sign up to set email alerts
|

Using XDMoD to facilitate XSEDE operations, planning and analysis

Abstract: The XDMoD auditing tool provides, for the first time, a comprehensive tool to measure both utilization and performance of high-end cyberinfrastructure (CI), with initial focus on XSEDE. Here, we demonstrate, through several case studies, its utility for providing important metrics regarding resource utilization and performance of TeraGrid/XSEDE that can be used for detailed analysis and planning as well as improving operational efficiency and performance. Measuring the utilization of high-end cyberinfrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The results revealed that PIs constituted 23% (3,334) of the total TeraGrid project users (14,474) and that molecular biosciences and chemistry are the two scientific fields with the highest number of projects involving TeraGrid usage, 2,292 and 1,828, respectively. Similarly, Furlani et al (2012Furlani et al ( , 2013a observed that molecular biosciences recently joined physics at the top of the list of sciences with the greatest CPU usage of Extreme Science and Engineering Discovery Environment (XSEDE), a virtual system providing digital resources and computing services (Towns et al, 2014). In addition, Furlani's longitudinal study demonstrated a substantial increase in the number of PIs using XSEDE from ~500 in 2005 to ~1,600 in 2011.…”
Section: Related Workmentioning
confidence: 98%
“…The results revealed that PIs constituted 23% (3,334) of the total TeraGrid project users (14,474) and that molecular biosciences and chemistry are the two scientific fields with the highest number of projects involving TeraGrid usage, 2,292 and 1,828, respectively. Similarly, Furlani et al (2012Furlani et al ( , 2013a observed that molecular biosciences recently joined physics at the top of the list of sciences with the greatest CPU usage of Extreme Science and Engineering Discovery Environment (XSEDE), a virtual system providing digital resources and computing services (Towns et al, 2014). In addition, Furlani's longitudinal study demonstrated a substantial increase in the number of PIs using XSEDE from ~500 in 2005 to ~1,600 in 2011.…”
Section: Related Workmentioning
confidence: 98%
“…Application kernel process control. 5 Process the output if it was collected. Indeed, the Copy it to HPC resource and submit to queue.…”
Section: Operation Overviewmentioning
confidence: 99%
“…Here, the IOR application kernel clearly shows a dramatic and sudden drop-off in write performance in January 2014. Additional application kernel success stories include (1) detection of a 25% degradation of NAMD performance after an 'upgrade' [3]; (2) detection of a software bug in the I/O stack of a commercial parallel file system that caused sporadic behavior in NWChem [5]; and (3) a sudden decrease in file system performance on TACC Lonestar4 as measured by three different application kernels (IOR, MPI-Tile-IO, and IMB) [6]. As shown in Figure 9, the file system performance was eventually returned to normal after working closely with the switch manufacturer and the vendor of the parallel file system.…”
Section: The Use Of Application Kernels To Assure Qosmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for this paper we will restrict our discussion to the IaaS based monitoring components. Other HPC related activities in regards to monitoring and metrics are discussed in [4].…”
Section: Monitoringmentioning
confidence: 99%